Территориальная организация с использованием возможностей развития природно-ориентированного туризма в Пермском крае (Географический вестник=Geographical bulletin, 2017)
Рассматривается территориальная организация ресурсного потенциала природно-ориентированного туризма в Пермском крае. Представлены результаты рейтинговой оценки и типологизации районов Пермского края по условиям развития туризма.THE TERRITORIAL ORGANIZATION WITH USE OF OPPORTUNITIES OF DEVELOPMENT OF THE NATURAL-FOCUSED TOURISM IN THE PERM EDGE The territorial organization of resources potential for nature-oriented tourism in the Perm Krai is disclosed. The results of the rating assessment and typology of the districts of the Perm Krai regarding their conditions for tourism development are presented.